Building Tolerance And Balance: A Systematic Literature Review On Religious Moderation Among Students In Higher Education - Ahmad Shofiyuddin; Siti Khoiriyah; Rangga Sa'adillah (Journal of Islamic Civilization, 2023)
In an increasingly complex global context, the role of religious moderation among higher education students is becoming increasingly important for promoting social harmony and intercultural dialogue. This article presents a systematic study that maps research studies on religious moderation in higher education using the Systematic Literature Review (SLR) method. The main objective of this study is to describe current research trends on religious moderation among college students, as well as identify important implications that can be drawn from such findings. The results of this SLR analysis revealed several key findings. First, research trends underscore the role of moderate character traits in shaping compassionate attitudes, positive thinking, strengthening religious commitment, and nurturing brotherhood among college students. Second, the research also shows that religious moderation can help minimize social conflict and create an inclusive environment on campus.second, it also has implications in shaping students' character and equipping them with the social skills needed in a diverse society.